EFFECT OF BEETROOT JUICE ON THE INCREASE IN HEMOGLOBIN LEVELS AMONG PREGNANT WOMEN AT KEMILING INPATIENT COMMUNITY HEALTH CENTER IN 2022 - wulandari, Lusia Asih Wulandari (Universitas Aisyah Pringsewu, 2024)
Anemia in pregnancy is a hemoglobin level below 11gr% in the 1st and 3rd trimesters or <10.5g% in the 2nd trimester. The pharmacological method to treat anemia is by administering Fe tablets and folic acid, while non-pharmacological treatment and prevention of anemia can be done by consuming beetroot. This study aims to determine the effect of beetroot juice on the increase in hemoglobin levels among pregnant women at Kemiling Inpatient CHC in 2022. This was a quantitative quasi-experimental study with one group pre-test and post-test approach. The samples involved 15 pregnant women in the third trimester with mild or moderate anemia at Kemiling Inpatient CHC. The study was conducted in January 2022. Data was collected using observation sheets. Data were analyzed using univariate and bivariate analysis (t-test). The results showed that the mean Hb level before and after the administration of beetroot juice was 10.46 gr/dl and 11.70 gr/dl, respectively. There was an effect of beetroot juice on the increase in hemoglobin levels among pregnant women at Kemiling Inpatient CHC in 2022 with a p-value of 0.000. Pregnant women need to find information about prevention and management of anemia in pregnancy and have regular prenatal checkups.